MONTREAL COGNITIVE ASSESSMENT VERSI INDONESIA MoCAIna UNTUK SKRINING GANGGUAN FUNGSI KOGNITIF - Nadia Husein*, Silvia Lumempouw*, Yetty Ramli*, Herqutanto** (NEURONA, 2010)
INTRODUCTION MOCA TEST IS VERY SENSITIVE IN MCI SCREENING THIS MOCA TEST ORIGINATED FROM CANADA WHICH IS DIFFERING IN TERMS OF CULTURE AND LANGUAGE FROM INDONESIA IN ORDER TO BE APPLICABLE IN INDONESIA MOCA TEST HAVE TO GO THROUGH VALIDITY AND RELIABILITY EXERCISES